Estimation of Gene Action and Interaction for Some Quantitative Characters in Rice (Oryza sativa L.) by Generation Mean Analysis - Kumari, Amrita; Senapati, B. K.; Aich, Anita Roy; Singh, Aditya Pratap (International Journal of Bio-resource and Stress Management, 2021)
The present investigation was conducted to understand the genetic action for controlling the inheritance of some quantitative characters. The experimental materials consisted of three rice varieties, i.e., Mahsuri, Bhutmuri, IR36 and F1, F2, and F3 populations of Mahsuri×Bhutmuri (Cross I) and IR36×Bhutmuri (Cross II). To conduct the generation mean analysis, the parents and their F1, F2, and F3 populations were evaluated during June to October month of Kharif 2016 and Kharif 2017. Generation mean analysis was done for eighteen quantitative characters following the five parameter model. The Analysis of Variance revealed significant differences among the five generations for all the characters studied. The results of the scaling tests and joint scaling test revealed that the Simple additive-dominance model was inadequate for days to 50% flowering, days to maturity, number of panicles plant-1, number of primary branches panicle-1, number of secondary branches panicle-1 in Cross I, while it was for plant height, number of tillers plant-1, number of panicles plant-1, number of grains panicle-1, number of filled grains panicle–1 and fertility % in Cross II. Hence, the present studies have revealed that epistasis as a basic mechanism that cannot be ignored. Thus, formulating breeding policies on only main gene effects i.e. additive and dominance could be misleading.